PERAN GURU DALAM MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA MELALUI PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Aulia Argierta; Zahratul Jannah; Erwin Efendi Hutagalung; Ayatullah Muhammadin Al Fath (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of teachers in improving students’ interest and motivation in learning through a deep learning approach in elementary school education. The research method used was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The subjects of this study were fourth-grade students of SDN 198/I Pasar Baru. Data collection techniques included observation, tests, and documentation. The results of the study indicate that the role of teachers as facilitators, motivators, and guides in implementing meaningful learning (deep learning) can enhance students’ engagement, interest, and learning motivation. This is reflected in the improvement of learning activities, students’ confidence in expressing their opinions, and their learning outcomes from cycle I to cycle II. Therefore, the deep learning approach is effective in improving the quality of learning in elementary schools.